Ultra-sensitive heterodyne detection at room temperature in the atmospheric windows - Saemian Mohammadreza; Del Balzo Livia; Gacemi Djamal; Todorov Yanko; Rodriguez Etienne; Lopez Olivier; Darquié Benoit; Li Lianhe; Davies Alexander Giles; Linfield Edmund; Vasanelli Angela; Sirtori Carlo (Nanophotonics)
We report room temperature heterodyne detection of a quantum cascade laser beaten with a local oscillator on a unipolar quantum photodetector in two different atmospheric windows, at 4.8 µm and 9 µm. A noise equivalent power of few pW is measured by employing an active stabilization technique in which the local oscillator and the signal are locked in phase. The measured heterodyne noise equivalent power is six orders of magnitude lower than that obtained with direct detection.